Universitas Psychologica: From Paper to Digital Formats - López López, Wilson; Pontificia Universidad Javeriana (2012)
From this issue on, our journal will be published only in a digital format. This jump in the dissemination of our contents is supported by our local, national and international visibility being mostly associated to our website, http://universitaspsychologica.javeriana.edu.co, as well as our presence in both open-access and proprietary databases, the increasing recognition of our contents made by our academic communities (the uses of our contents in terms of citations and downloads), and other uses associated to the impact in student training or other social appropriations of knowledge that we have been making more visible (essentially dissemination through mass media). We understand that this change will require new efforts to improve processes and response times to the authors. We have received more than 1900 articles in the past two years, and we have more than 300 currently undergoing peer-review. We understand that our communities area learning, and that these processes involve both time and complexities that we were not quite ready for. In order to alleviate this situation, we have committed ourselves to publish one more issue every year, and a special issue at the end of 2012. Wilson López Lopez Editor